Pemanfaatan Digital Marketing dan Penerapan Packaging Dalam Pengembangan Bisnis: Studi di 3 Japanese Food di Kota Malang - Sulaiha, Sulaiha; Munfaqiroh, Siti (STIE Widya Manggala, 2024)
This research aims to explain the benefits of digital marketing and the application of packaging in business development at 3 Japanese food in Malang City. Apart from that, this research also reveals what happens if you don’t implement digital marketing and packaging in business development. The research results show that here are changes before and after utilizing digital marketing and implementing packaging in business development at 3 Japanese foods in Malang City.